Pros and Cons of Use of Mitochondria-Targeted Antioxidants - Egor Y. Plotnikov; Dmitry B. Zorov (Antioxidants, 2019)
Mitochondrial targeting is a novel strategy, which addresses pathologies originating from mitochondrial dysfunction. Here, one of the most potent therapeutics arises from the group of mitochondria-targeted antioxidants, which specifically quench mitochondrial reactive oxygen species (ROS). They show very high efficacy in the treatment of a diverse array of pathologies encountered in this Special Issue of Antioxidants. However, despite very encouraging results in the use of mitochondria-targeted antioxidants, the mechanistic principle of delivering these agents is, to some extent, counterproductive to the goal of selectively treating a population of damaged mitochondria. The main problem that arises is that injured mitochondria may carry a lower membrane potential when compared with normal ones and as a result, injured mitochondria are capable of taking up less therapeutic antioxidants than healthy mitochondria. Another problem is that the intracellular activity of mitochondrial ROS differs from cytosolic ROS in that they carry specific intracellular functions which are maintained at a delicate equilibrium and which may be disturbed under careless use of antioxidant doses. Consequently, understanding the overall benefit of targeting dysfunctional mitochondria in pathological tissue requires furthering the development of alternative techniques to target mitochondria.